Guderian : panzer pioneer or myth maker? - Hart, Russell A. ([S.l.] : Pentagon Press, 2010)
While it remains one of the most widely read accounts of World War II, Russell A. Hart argues that too many of Guderian's biographers have accepted his view of his accomplishments at face value, without sufficient critical scrutiny. Unfortunately, an undeserved hagiography has resulted. While undoubtedly a great military figure of appreciable ego and ambition and with a volatile, impetuous, and difficult personality, Guderian was determined to achieve his vision of a war-winning armored force irrespective of the consequences. He proved to be a man who was politically naive enough to fall under the sway of Hitler and National Socialism and yet arrogant enough to believe he could save Germany from inevitable defeat late in the war, despite Hitler's interference. At the same time, Guderian failed either to participate in attempts to remove Hitler or to denounce as traitors the conspirators who did. In the end, he twisted the truth to establish his place in history. In the process, he denigrated the myriad important contributions of his fellow officers as he took personal credit for what were, in reality, collective accomplishments. Thus, he succeeded in creating a legend that has endured long after his death. This brief biography puts the record straight by placing Guderian's career and accomplishments into sharper and more accurate relief. It exposes the real Heinz Guderian, not the man of legend.